Managing Local Wisdom-Based Curriculum: An Integrative Framework for Madrasah Education - Cut Irhamna Heriyanti; Amiruddin Siahaan; Siti Halimah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze and develop a curriculum model grounded in local wisdom for madrasas. The study focuses on curriculum planning, implementation, and evaluation, as well as a comparison of implementation across two madrasas. A qualitative case study approach was used, and data were collected through in-depth interviews, observation, and documentation with informants, including madrasah principals, teachers, and madrasah committees. The results indicate that curriculum planning was carried out in a participatory manner, integrating local cultural and Islamic values into objectives, materials, methods, and evaluation. Curriculum implementation included religious habituation, experiential learning, arts and culture, memorization of the Qur'an and Hadith, and social activities based on local culture. Evaluation was conducted authentically by assessing cognitive, affective, and psychomotor aspects through observations of student behavior, cultural practices, religious habituation, and learning outcomes. One madrasah emphasized a contextual approach grounded in school culture, while the other emphasized a structured, measurable religious program. This research produces an integrative curriculum model that combines local culture, religious learning, contextual experiences, authentic evaluation, and community participation as a framework for educational development.